Non-equilibrium molecular dynamics simulation of anisotropic heat transfer and thermal conductivity of single crystalline magnesium antimonide - Gunay, Seckin D.; Akdere, Unsal; Taseven, Cetin (ELSEVIER, 2025)
Magnesium antimonide (Mg3Sb2) based materials are potential candidates as thermoelectric materials in thermoelectric devices with enhanced performance. Thermal conductivity and its temperature dependence are key factors in their practical applications. The present work aims to evaluate the temperature dependence of lattice thermal conductivity (kappa(L)) of single crystalline Mg3Sb2 along the in-plane and out-of-plane directions between 300K and 700K. Non-equilibrium molecular dynamics (NEMD) simulation combined with two regions thermostatting method is followed to mimic the real experiment. It is found that the kappa(L) exhibits strong anisotropy at low and mid temperatures and becomes nearly isotropic at high temperatures. The kappa(L) is significantly low along both in-plane and out-of-plane directions, and reduces from similar to 2.1 to similar to 1.1 W m(-1)K(-1)and similar to 1.3 to similar to 1.1 W m(-1)K(-1), respectively, but with different temperature dependences. Deviating from the typical T-1 law, calculated kappa(L) demonstrates an anomalously weaker temperature dependence in the in-plane direction described as T-0.67, and even weaker in the out-of-plane direction as T-0.14. Anisotropic low thermal conductivity is crucial for searching thermoelectric materials with enhanced figure of merit, and hence this work may provide guideline and encourage future studies on Mg3Sb2 based materials.
Keywords: Magnesium antimonide; Non-equilibrium molecular dynamics; Thermal conductivity; THERMOELECTRIC PROPERTIES; IRREVERSIBLE-PROCESSES; MG3SB2; PERFORMANCE; COMPOUND; LIQUID; SB; Materials Science